2011
DOI: 10.1002/adma.201100408
|View full text |Cite
|
Sign up to set email alerts
|

Superheated Rubber for Cold Storage

Abstract: Supercooled liquids are still considered to be magic materials that can store heat, which is easily to be released with a suited trigger. Storage of cold is much harder to achieve, e.g., by using superheated liquids or liquifi ed gases, which are naturally hard to handle and require laborious equipment. Storing cold with solid materials is not yet realized because superheated solids are generally assumed to be impossible. [ 1 ] Here we report on designed natural rubber (NR) networks that can store cold and rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
79
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 76 publications
(86 citation statements)
references
References 15 publications
4
79
1
2
Order By: Relevance
“…Intriguingly, recent study has shown that polymer crystals formed via strain-induced crystallization can be manipulated to precisely tune the melting temperature [312][313][314]. This may open up new ways to induce 2W-SME.…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, recent study has shown that polymer crystals formed via strain-induced crystallization can be manipulated to precisely tune the melting temperature [312][313][314]. This may open up new ways to induce 2W-SME.…”
Section: Discussionmentioning
confidence: 99%
“…[ 10 ] The set of properties can be greatly enhanced by blending, [11][12][13][14][15] functional groups, [16][17][18] and additives. [ 20,21 ] It was found that whenever NR is vulcanized below a critical degree of crosslinking, it generates crystals upon strain that are stable at room temperature and can thus stabilize a programmed shape. One way to achieve this is to design a material that allows re-arrangement of its microstructure by such an external stimulus, which then stays intact after removing the stimulus.…”
Section: Doi: 101002/adma201305698mentioning
confidence: 99%
“…Recently, we reported on lightly cross‐linked shape‐memory natural rubber (SMNR) with superior properties. Firstly, SMNRs are one of the few materials that can be programmed without additional heating (cold programmability) 23. Secondly, SMNR is the first example of a semi‐crystalline SMP with a significantly tunable trigger temperature 23.…”
Section: Introductionmentioning
confidence: 99%